2020
DOI: 10.1002/mawe.202000057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erbium on microstructure and mechanical properties of Al‐Si‐Mg‐Cu alloy

Abstract: The effect of erbium addition at different ratios (0.2 wt.%, 0.4 wt.%, 0.6 wt.%) on microstructure evolution and mechanical properties of the AlÀ Si-MgÀ Cu alloy have been investigated. The results show that adding erbium can refine the primary αaluminum grains in the as-cast alloys to a diverse extent. In addition, the coarse and long plate-like eutectic silicon can be modified into a fine short rod-like structure, and the distribution of eutectic silicon can be optimized. During the solidification of the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…On the one hand, the grain size of the alloy becomes uneven, which affects the mechanical properties of the material; on the other hand, when the amount of Er added exceeds 0.6 wt.%, in addition to the formation of the Al 3 Er phase, a portion of the AlCuEr phase may be formed, which reduces the mechanical properties of the alloy. Lei added Er to an Al-Si-Mg-Cu alloy and also found that the addition of 0.6 wt.% erbium has a greater promotion effect than an inhibition effect, and the alloy has the best mechanical properties at as-cast and heat-treatment conditions [29].…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…On the one hand, the grain size of the alloy becomes uneven, which affects the mechanical properties of the material; on the other hand, when the amount of Er added exceeds 0.6 wt.%, in addition to the formation of the Al 3 Er phase, a portion of the AlCuEr phase may be formed, which reduces the mechanical properties of the alloy. Lei added Er to an Al-Si-Mg-Cu alloy and also found that the addition of 0.6 wt.% erbium has a greater promotion effect than an inhibition effect, and the alloy has the best mechanical properties at as-cast and heat-treatment conditions [29].…”
Section: Tensile Propertiesmentioning
confidence: 99%